Field-validated multiplex RT-qPCR for simultaneous detection of bovine respiratory syncytial virus and bovine parainfluenza virus-3 in bovine respiratory samples - Zulauf, Brian; Pastey, Manoj K. (Frontiers in Veterinary Science, 2025)
Bovine respiratory syncytial virus (BRSV) and bovine parainfluenza virus Type 3 (BPIV3) are ubiquitous respiratory pathogens of cattle, contributing significantly to the bovine respiratory disease (BRD) complex. Rapid and reliable detection methods are essential to mitigate economic losses and improve animal welfare. This study aimed to develop and validate sensitive and specific reverse transcriptase quantitative real-time PCR (RT-qPCR) assays for the simultaneous detection of BRSV and BPIV3 in bovine respiratory samples. Primers and dual-labeled probes were designed from GenBank sequences targeting conserved regions of the BRSV N gene and BPIV3 NP gene and optimized for sensitivity and specificity. The assays were evaluated using reference strains, field isolates, and clinical samples. Analytical sensitivity was established through serial dilutions of in vitro transcribed RNA and confirmed by probit regression analysis, yielding LOD95 values of 164 genome copies for BRSV and 359 genome copies for BPIV3. The assays demonstrated high specificity (no cross-reactivity with non-target bovine respiratory viruses), and reproducibility (CV < 5%). Standard curves demonstrated strong linearity (R2 > 0.99) with amplification efficiencies of 104.2% for BRSV and 81.6% for BPIV3. Diagnostic performance was evaluated on 100 clinical samples, with monoplex RT-qPCR detecting BRSV in 19% and BPIV3 in 11% of cases, outperforming virus isolation. The multiplex assay detected 17% BRSV and 7% BPIV3 positives of cases in a single reaction. Compared to traditional virus isolation, the RT-qPCR assays detected 2.4 × more BRSV and reliably identified BPIV3-positive cases that were otherwise missed. These assays offer a robust diagnostic solution for high-throughput screening in clinical and surveillance settings.